Design and implementation of wireless distributed communication system - Liu, Xiaolin. (2008)
This thesis presents the design and implementation of a Wireless Distributed COmmunication System (WDCS). The application environment addressed by our WDCS is an underground tunnel, namely a mine tunnel.